Construction of a genetic map of human chromosome 17 by use of chromosome-mediated gene transfer. - Xu, W M (1988)
We used somatic-cell hybrids, containing as their only human genetic contribution part or all of chromosome 17, as donors for chromosome-mediated gene transfer. A total of 54 independent transfectant clones were isolated and analyzed by use of probes or isoenzymes for greater than 20 loci located on chromosome 17. By combining the data from this chromosome-mediated gene transfer transfectant panel, conventional somatic-cell hybrids containing well-defined breaks on chromosome 17, and in situ hybridization, we propose the following order for these loci: pter-(TP53-RNP2-D17S1)-(MYH2-MYH1)-D17Z 1-CRYB1-(ERBA1-GCSF-NGL)-acute promyelocytic leukemia breakpoint-RNU2-HOX2-(NGFR-COLIAI-MPO)-GAA-UM PH-GHC-TK1-GALK-qter. Using chromosome-mediated gene transfer, we have also regionally localized the random probes D17S6 to D17S19 on chromosome 17.